2021
DOI: 10.1098/rspb.2020.2896
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure in the endosymbiont Breviolum ‘muscatinei’ is correlated with geographical location, environment and host species

Abstract: Corals and cnidarians form symbioses with dinoflagellates across a wide range of habitats from the tropics to temperate zones. Notably, these partnerships create the foundation of coral reef ecosystems and are at risk of breaking down due to climate change. This symbiosis couples the fitness of the partners, where adaptations in one species can benefit the holobiont. However, the scales over which each partner can match their current—and future—environment are largely unknown. We investigated population geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…after bleaching [23][24][25], the net benefit of the symbiosis to each partner could decline. Furthermore, if bleaching resistance comes at the expense of another trait such as growth [19], individuals might escape the acute risk to their fitness due to bleaching today, only to experience lower fitness later in life in the form of reduced reproductive output. Evolved responses to increased heat stress might not doom corals as a species or population but could profoundly restructure ecosystems where both productivity and persistence rely on the current balance of nutritional exchange between corals and their dinoflagellate partners.…”
Section: A Sea Of Corpses or Flourishing With Life?mentioning
confidence: 99%
See 2 more Smart Citations
“…after bleaching [23][24][25], the net benefit of the symbiosis to each partner could decline. Furthermore, if bleaching resistance comes at the expense of another trait such as growth [19], individuals might escape the acute risk to their fitness due to bleaching today, only to experience lower fitness later in life in the form of reduced reproductive output. Evolved responses to increased heat stress might not doom corals as a species or population but could profoundly restructure ecosystems where both productivity and persistence rely on the current balance of nutritional exchange between corals and their dinoflagellate partners.…”
Section: A Sea Of Corpses or Flourishing With Life?mentioning
confidence: 99%
“…Though the same evolutionary forces that shape host populations are at work in their symbionts, microorganisms can adapt to local conditions across smaller temporal and spatial scales than their hosts. Genetic evidence suggests that symbiont populations can match their local environment, which can change over a few meters in temperate systems with large environmental gradients such as the intertidal zone [ 19 ]. Additionally, Symbiodiniaceae generation time is short, allowing them to match temporal variation at timescales of weeks to months that would be impossible for their hosts, who typically live for years if not decades or centuries.…”
Section: A Sea Of Corpses or Flourishing With Life? Effects Of Warmin...mentioning
confidence: 99%
See 1 more Smart Citation
“…A particularly important feature of the A. sola expansion is that they are likely encountering novel symbiont populations that historically have only interacted with 2 other symbiotic species that are members of the genus Anthopleura , A. xanthogrammica and A. elegantissma whose geographic ranges extend to Alaska. Previous work has shown that these symbionts are shared between these 3 species—with the exception of the southernmost populations of A. sola and A. elegantissima , where symbionts are partitioned by host species ( Cornwell and Hernández 2021 ). As A. sola continues to move northward, interactions between newly arriving hosts and naive symbiont populations will become more common, which will allow researchers to identify patterns of molecular and physiological coevolution in both partners as geographic ranges shift with climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Well-assembled genomes are an important tool for identifying genomic patterns associated with range expansions and coevolution with symbiont partners. A. sola exhibits little population structure across its geographic range with no evidence for historical population bottlenecks, which likely contributes to the highest average level of heterozygosity of the 3 symbiotic species of Anthopleura on the Pacific coast of North America ( π = 0.0095; Cornwell and Hernández 2021 ). A draft assembly of A. sola has already been generated without long reads, resulting in a contig N50 of 5,224 bp and scaffold N50 of 16,096 with a total estimated genome size of 434 Mb ( Cornwell 2020 ).…”
Section: Introductionmentioning
confidence: 99%